Making European Merger Policy More Predictable - Voigt, Stefan; Schmidt, André (Springer US : Imprint: Springer, 2005)
Making European Merger Policy More Predictable analyses European Merger Control with regard to its capacity to generate predictability among the concerned parties. Starting from the premise that predictability is of overwhelming importance for the functioning of market economies, Voigt and Schmidt ask to what degree European Merger Control has been predictable over the last couple of years. The authors show both theoretically and empirically that there have been serious shortcomings with regard to the predictability of competition policy. They identify the insufficient recognition of the consequences of globalization on the competitive processes as well as an often inconsistent application of economic theory as the root causes for the lack of predictability. The inconsistent application of economic theory is particularly relevant with regard to potential competition and the evaluation of collective dominance. The authors generate a substantial number of proposals that could help to improve predictability. On this basis, Voigt and Schmidt critically assess the recent reforms of European Merger Control.